Sistem Nilai dalam Al-Imarah - Haji Hassan, Abdullah Alwi (Jurnal Usuluddin, 1995)
This article discusses briefly the system of value in al-'Imarah according to Islamic perspective. In islam, al-'Imarah is defined as a total development of human being, whether physically or spiritually, which may lead to a true human civilization. To achieve this end, al-'Imarah has to be based on, inter alia, the world-view of tawhid (belief in the unity of god), the concepts of khilafah (vicegerency of man) and amanah (trust-neorthiness), and also on allen compassing ethical practicality of the syari'ah (the revealed law of Islam). With these principles only man can alleviate the present spiritual and technological crisis in order to build a new and stable civilization in this world.